Evaluación de la calidad de una sesión de registro simultáneo de la fuerza oclusal y la actividad electromiográfica del músculo masetero - Peláez V., Alejandro; Álvarez, Marta E.; Gaviria B., María Isabel; Gallego R., Gabriel (Revista Mexicana de Ingenieria Biomedica, 2003)
The aim of the present investigation was to evaluate the quality of a session of simultaneous registration of bite force and AEMG in a group of 19 young adults, during four functional tasks: maximal opening, maximal cuspation, bite on the gnatodinamometer on the right side and bite on the gnatodinamometer on the left side. Three registrations were obtained for each task in one day. A grouped descriptive, a global and an individual analysis of the data was performed. It was found a high correlation when evaluating the symmetry of the AEMG registration in maximal opening (r = 0.83) and bite force (r = 0.92) and it was not found a good correlation in the EMG registration neither in maximal cuspation (r = 0.46) nor in the right and left masseter muscle during the unilateral bite on each side, when analyzing the EMG of the work and balance side.